2016
DOI: 10.7314/apjcp.2016.17.2.519
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequency of Oral Malignancies and Oral Precancer in the Biopsy Service of Jazan Province, 2009-2014

Abstract: Background: The objective of this study was to report the types and relative frequency of oral malignancies and precancer in the Jazan region of Saudi Arabia during the period 2009-2014. Materials and Methods: Pathology reports were retrieved from the archives of Histopathology Department, King Fahd hospital in Jazan. Demographic data on tobacco habits, clinical presentation and histologic grading of oral precancer and cancer cases were transcribed from the files. Results: 303 (42.7%) oral pre-malignant and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 35 publications
1
31
2
Order By: Relevance
“…In phase‐2, 313 studies were excluded (Appendix ). In the final review, 22 studies were included for qualitative and quantitative evaluation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In phase‐2, 313 studies were excluded (Appendix ). In the final review, 22 studies were included for qualitative and quantitative evaluation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 22 studies selected, 7 studies were performed in South America's or Caribbean countries, 5 in Asia, 5 in Europe, 2 in the Middle East, and 2 in North America . Six of the included studies had a sample size lower than 1000 individuals, and 4 studies had their sample size larger than 50 000 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported the duration of shammah use among the study groups and ranged from 10 to 45 years and 1 to 12.5 minutes per serving. The reported odds ratio was 6.91 (95% CI: 2.66‐17.95) for an average duration of shammah use of >5 minutes and 1.07 (95% CI: 0.98‐1.17) for the duration of being a shammah user of more than 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…While assessing the quality of included studies using NOS score, only three were classified as good‐quality studies . These reported cancer cases that were confirmed either through histological analysis or hospital records and adjusted their risk estimates for other confounding factors including smoking.…”
Section: Discussionmentioning
confidence: 99%